2008
DOI: 10.1016/j.ocemod.2007.07.001
|View full text |Cite|
|
Sign up to set email alerts
|

Explicit wave-averaged primitive equations using a generalized Lagrangian mean

Abstract: The generalized Langrangian mean theory provides exact equations for general wave-turbulence-mean flow interactions in three dimensions. For practical applications, these equations must be closed by specifying the wave forcing terms. Here an approximate closure is obtained under the hypotheses of small surface slope, weak horizontal gradients of the water depth and mean current, and weak curvature of the mean current profile. These assumptions yield analytical expressions for the mean momentum and pressure for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
188
1
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(194 citation statements)
references
References 66 publications
(81 reference statements)
2
188
1
3
Order By: Relevance
“…The obtained set of equations is nondivergent, thanks to a transformation of the vertical coordinate. The A08 formulation is consistent with Mc Williams et al [2004] to the considered order of approximation in the limit of a weak mean-current vertical shear [Ardhuin et al, 2008b]. Bennis et al [2011] confirmed the ability of A08 formulation to provide the vertical structure of the flow by numerical modeling of an adiabatic configuration.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…The obtained set of equations is nondivergent, thanks to a transformation of the vertical coordinate. The A08 formulation is consistent with Mc Williams et al [2004] to the considered order of approximation in the limit of a weak mean-current vertical shear [Ardhuin et al, 2008b]. Bennis et al [2011] confirmed the ability of A08 formulation to provide the vertical structure of the flow by numerical modeling of an adiabatic configuration.…”
Section: Introductionsupporting
confidence: 84%
“…The new code version solves the glm2z asymptotic formulation of the GLM wave-current equations for the quasi-Eulerian momentum, as proposed by Ardhuin et al [2008b] and further adapted by Bennis et al [2011]. The quasi-Eulerian velocity field, noted u5ðû 1 ;û 2 ;ŵÞ, is defined as [Jenkins, 1989] …”
Section: Flow Model Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…The ongoing debate about the vertical distribution of wave-induced radiation stresses that generally split up into a surface component, a bottom component and a body force and their implementation within 3-D momentum equations (discussed in, for example, Ardhuin and Roland, 2013;Ardhuin et al, 2008;Bennis et al, 2011) reflects on and indicates that important wave-induced processes interacting with the flow circulation may still be inadequately implemented in Delft3D. These model limitations are, however, accepted in the present study assuming minor effects on the sedimentology and morphology at the tidal inlet.…”
Section: Modeling Systemmentioning
confidence: 99%
“…2 We show here 54 that the VWS is contained in the Favre-filtered momentum equations. Indeed, we are able to reproduce 55 the equations used by all these previous authors and are able to point out the different surface fluxes of 56 momentum that are implicit in these papers and that account for the differences between the different 57 2 To our knowledge no previous studies, except for an attempt by Ardhuin et al (2008), have used the Generalized Lagrangian Mean equations of Andrews and McIntyre (1978) to explain the VWS. ), will be discussed in a later paper in the context of the Favre-filtered equations in the VL coordinate 61…”
mentioning
confidence: 85%